Letter Forms as Communicative Urban Artifacts for Social Narratives - Muhammad Rahman; Vikas Mehta (Interdisciplinary Journal of Signage and Wayfinding, 2018)
Words, type and letters - as signs and artifacts - have an immense promise to convey meaning in the urban environment. Letterforms are the 'architecture of language' (Baines and Haslam, 2005) - they build narratives, and create inquisitive interpretive spaces through which the reader experiences meaning. Typography and letterforms can possibly be perceived and defined in two ways - functional (legibility) and visual (formal). The utilitarian domain of typography is a prerequisite for effective communication, but letterforms have also been an unsolved quest for designers to explore and qualify various other more ephemeral dimensions of communication. Unique to letterforms is the distinctive manner in which they can be used to occupy space, convey characteristics, portray personality and physique, and situate dimensionally or even be associated with variety of emotions. Type is an art form, providing immense pleasure to the everyday observer, reader and speculator.